2004
DOI: 10.1536/jhj.45.771
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Brain Natriuretic Peptide, Myocardial Wall Stress, and Ventricular Arrhythmia Severity

Abstract: SUMMARYWe previously demonstrated that the severity of arrhythmias is reflected by circulating brain natriuretic peptide (BNP) concentrations in patients without signs of congestive heart failure. In the present study, we evaluated the relationships between the severity of the arrhythmia, BNP concentration, and echocardiographic findings.The subjects consisted of 52 patients with ventricular premature contractions (VPC) but no manifestations of heart failure and no digoxin or beta-blocker therapy. Patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Indeed, in patients with essential hypertension, both ANP and BNP levels are positively correlated with posterior wall thickness (LVPW) [29]. In patients with premature ventricular contractions, BNP levels are positively correlated with LVPW [30]. Consistent with this, we found a significant positive correlation between BNP expression and LVPW.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, in patients with essential hypertension, both ANP and BNP levels are positively correlated with posterior wall thickness (LVPW) [29]. In patients with premature ventricular contractions, BNP levels are positively correlated with LVPW [30]. Consistent with this, we found a significant positive correlation between BNP expression and LVPW.…”
Section: Discussionsupporting
confidence: 80%
“…Plasma BNP is also a useful index of therapeutic outcome during drug treatment for heart failure 7) and a response to abnormal wall stress from severe ventricular arrhythmias. 8) Some investigations in Japanese subjects have shown that plasma BNP is useful as an independent factor for estimation of the outcome and prediction of sudden death. 9,10) On the other hand, plasma BNP has been reported to increase with increases in the grade of severity of heart disease according to the NYHA classification in a way similar to the plasma levels of ANP, cGMP, and norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in both BNP and NT-proBNP plasma levels have been observed in association with cardiac myocyte stretching, and in arrhythmias [2][3][4]. B-type natriuretic peptides have therefore recently gained attention as biomarkers of cardiac arrhythmic syncope [5,6].…”
mentioning
confidence: 99%
“…The present study analysed a subgroup of patients from the APACE ongoing cohort [3] with final adjudicated diagnosis of UA or NSTEMI who had coronary angiograms during the course of hospitalization.…”
mentioning
confidence: 99%